2021
DOI: 10.1039/d0cp05435f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single and double active sites of Cu oxide clusters over the MFI zeolite for direct conversion of methane to methanol: DFT calculations

Abstract: In this work, we investigate the effect of various species of Cu oxide clusters including single and double active sites incorporated in the MFI zeolite framework for the direct conversion of methane to methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Reaction (1) in Scheme depicts the formation of methanol effected by a single mono-μ-oxo dicopper­(II) site, which has been described extensively in the literature and likely proceeds via the “radical rebound” mechanism. ,,, Spectroscopic studies have provided extensive evidence that methanol formation over Cu zeolites involves the formation of methoxy ,,,,,, and/or adsorbed methanol ,,,,, , surface intermediates. The formation of methanol at mono-μ-oxo dicopper­(II) sites is supported by our observation of a positive correlation between methanol yield and relative intensity of the Cu-MOR UV–vis spectra at 27 500 cm –1 (Figure ), a feature which we attribute to mono-μ-oxo dicopper­(II) species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction (1) in Scheme depicts the formation of methanol effected by a single mono-μ-oxo dicopper­(II) site, which has been described extensively in the literature and likely proceeds via the “radical rebound” mechanism. ,,, Spectroscopic studies have provided extensive evidence that methanol formation over Cu zeolites involves the formation of methoxy ,,,,,, and/or adsorbed methanol ,,,,, , surface intermediates. The formation of methanol at mono-μ-oxo dicopper­(II) sites is supported by our observation of a positive correlation between methanol yield and relative intensity of the Cu-MOR UV–vis spectra at 27 500 cm –1 (Figure ), a feature which we attribute to mono-μ-oxo dicopper­(II) species.…”
Section: Resultsmentioning
confidence: 99%
“…We propose that two μ-1,2-peroxo dicopper­(II) species are involved in the formation of CO 2 based on the correlation in Figure between the UV–vis peak at ∼22 000 cm –1 (assigned to the μ-1,2-peroxo dicopper­(II) species) and the CO 2 yield, as well as the requirement of four oxygen atoms for CO 2 formation from methane. A recent quantum chemical study demonstrated the feasibility of a pair of μ-1,2-peroxo dicopper­(II) sites activating methane in Cu-exchanged ZSM-5 …”
Section: Resultsmentioning
confidence: 99%
“…Active site heterogeneity is a key concept in heterogeneous catalysis and a primary challenge is identifying active sites and their distribution. Active site heterogeneity can stem from differences in ligands and atomic environments, , including variations in the nuclearity of metal active sites. Materials containing a distribution of metal active site nuclearities can show drastic differences in reactivity for reactions including ethylene hydrogenation, D 2 exchange in CH 4 , and partial methane oxidation (PMO). , Copper-exchanged zeolites in particular have shown sensitivity to active site nuclearity for a number of reactions including the selective catalytic reduction (SCR) of NO x ,, catalytic or stepwise PMO, ,, and NO oxidation . Here, we develop condition-dependent computational models for Cu speciation in a wide variety of zeolite topologies and compositions.…”
Section: Introductionmentioning
confidence: 99%